2015
DOI: 10.1002/mgg3.160
|View full text |Cite
|
Sign up to set email alerts
|

Identification of point mutations and large intragenic deletions in Fanconi anemia using next‐generation sequencing technology

Abstract: Fanconi anemia (FA) is a rare bone marrow failure disorder characterized by clinical and genetic heterogeneity with at least 17 genes involved, which make molecular diagnosis complex and time‐consuming. Since next‐generation sequencing technologies could greatly improve the genetic testing in FA, we sequenced DNA samples with known and unknown mutant alleles using the Ion PGM ™ system (IPGM). The molecular target of 74.2 kb in size covered 96% of the FA‐coding exons and their flanking regions. Quality control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Therefore, genome-wide CNV analysis should be considered in IBMFS cases where nucleotide-level sequencing does not reveal the causal mutation or in cases with autosomal recessive disorders where only one pathogenic allele was found by nucleotide-level analysis. According to our analysis this is true not only for Diamond–Blackfan anemia and Fanconi anemia patients as suggested previously, 22 26 but in general for patients with suspected IBMFS. The costs associated with this additional analysis are relatively modest.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, genome-wide CNV analysis should be considered in IBMFS cases where nucleotide-level sequencing does not reveal the causal mutation or in cases with autosomal recessive disorders where only one pathogenic allele was found by nucleotide-level analysis. According to our analysis this is true not only for Diamond–Blackfan anemia and Fanconi anemia patients as suggested previously, 22 26 but in general for patients with suspected IBMFS. The costs associated with this additional analysis are relatively modest.…”
Section: Discussionsupporting
confidence: 86%
“… 21 Cases of IBMFSs with pathogenic CNVs have been reported previously, most notably in Diamond–Blackfan anemia 22 24 but also in Fanconi anemia. 25 , 26 In particular, an association of these types of mutations with neurodevelopmental delay 22 and short stature 23 has been suggested in small series of patients with Diamond–Blackfan anemia.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the coverage of the RBM8A amplicons was reduced respect to that of amplicons of other genes (data not shown). Then, to assess whether the IPGM data could be used for detection of CNVs , we determined whether the analysis of WAS, GATA1, and FLNA , the three genes of our target design located on chromosome X, could assign the gender of the probands. Analyzing the intersample normalization ratio of all the amplicons covering the three genes, we found that the median was below 0.7 in both the probands (0.6 and 0.5 in the proband of family 1 and 2, respectively), according to the hemizygous condition of chromosome X in males (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…This testing strategy has the advantage of allowing many genes to be tested at the same time, which limits waiting periods involved with sequential testing and, as the costs are falling, may possibly replace the use of chromosome breakage and single-gene analysis for FA diagnostics. [39] A number of commercially available NGS panel tests are available through international laboratories.…”
Section: Diagnosismentioning
confidence: 99%